2008
DOI: 10.1002/pmic.200701049
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of hearts from frataxin knockout mice: Marked rearrangement of energy metabolism, a response to cellular stress and altered expression of proteins involved in cell structure, motility and metabolism

Abstract: A frequent cause of death in Friedreich's ataxia patients is cardiomyopathy, but the molecular alterations underlying this condition are unknown. We performed 2-DE to characterize the changes in protein expression of hearts using the muscle creatine kinase frataxin conditional knockout (KO) mouse. Pronounced changes in protein expression profile were observed in 9 week-old KO mice with severe cardiomyopathy. In contrast, only several proteins showed altered expression in asymptomatic 4 week-old KO mice. In hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 58 publications
1
21
1
Order By: Relevance
“…29 As already mentioned, FXN plays an important role in mitochondrial iron homeostasis. 12,13 In wild-type mice, we found increased levels of FXN mature protein after lesion, whereas the precursor form was not elevated. In contrast, although levels of the precursor protein were significantly increased in transgenic as compared to wildtype mice, the mature protein was not changed after lesion.…”
Section: Frataxin Overexpression Increases Rgc Survival After Acute Imentioning
confidence: 64%
See 1 more Smart Citation
“…29 As already mentioned, FXN plays an important role in mitochondrial iron homeostasis. 12,13 In wild-type mice, we found increased levels of FXN mature protein after lesion, whereas the precursor form was not elevated. In contrast, although levels of the precursor protein were significantly increased in transgenic as compared to wildtype mice, the mature protein was not changed after lesion.…”
Section: Frataxin Overexpression Increases Rgc Survival After Acute Imentioning
confidence: 64%
“…10,11 Although the biological functions of FXN are still not fully understood, the protein serves important functions in iron homeostasis and biogenesis of iron-sulphur clusters in active sites of the complexes I and II of the mitochondrial electron transport chain and aconitase. 12,13 Cells that are deficient in FXN appear to be less efficient at generating natural antioxidant factors.14 There is evidence indicating that increasing FXN reduces the effects of oxidative stress and increases cell survival after oxidative stress-induced cell death. 3,4,15,16 Retinal ischemia/hypoxia is a complication of ocular diseases such as diabetic retinopathy, retinopathy of prematurity, and glaucoma.…”
mentioning
confidence: 99%
“…In this study, Fdxr up-regulation may be related to heme a synthesis, which is required for oxidative phosphorylation. Our proteomic studies have shown that frataxin depletion leads to energy metabolism deficiencies in MCK mutants, leading to metabolic compensation in an attempt to overcome the deficit (24). This may explain the Fdxr up-regulation.…”
Section: Frataxin Deficiency In the Heart Leads To Suppression Of Promentioning
confidence: 91%
“…Our aim was to explore the changes in iron metabolism due to frataxin deficiency. These mutants exhibit classical traits of the cardiomyopathy in Friedreich's ataxia, including cardiac hypertrophy, ISC enzyme deficiency, and marked mitochondrial iron accumulation (7,11,24). Thus, this model closely reflects the cardiac pathology in Friedreich's ataxia.…”
mentioning
confidence: 99%
“…This ISC enzyme is critical for MIT energy metabolism and is markedly decreased in the mutant compared to WT (5,19). When we examined 8.5-weekold mice treated with vehicle or PIH/DFO, it was clear the chelators did not prevent the decrease in SDHA expression (Fig.…”
Section: Marked Alterations In Cytosolic 59 Fe Distribution Within Fementioning
confidence: 99%